Good Rosie! - DiCamillo, Kate; Bliss, Harry, 1964- (Somerville, Massachusetts : Candlewick Press, 2018)
Rosie is a good dog and a faithful companion to her owner, George. She likes taking walks with George and looking at the clouds together, but the closest she comes to another dog is when she encounters her reflection in her empty dog bowl, and sometimes that makes Rosie feel lonely. One day George takes Rosie to the dog park, but the park is full of dogs that Rosie doesn't know, which makes her feel lonelier than ever. When big, loud Maurice and small, yippy Fifi bound over and want to play, Rosie's not sure how to respond. Is there a trick to making friends? And if so, can they all figure it out together?
In English.
Keywords: Dogs -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Loneliness -- Comic books, strips, etc. -- Juvenile fiction; Dogs -- Fiction; Friendship -- Fiction; Loneliness